Evaluasi Penerapan Standar Akuntansi Pemerintahan Berbasis Akrual Pada BPKAD Kabupatan Mahakam Ulu - Umi Kulsum, Rebecca Vivi Arriany Imam Nazarudin Latif, (EKONOMIA, 2021)
This study aims to find out and analyze the financial statements of BPKAD Mahulu Regency on the application of the balance sheet with SAP No. 01 of 2010 concerning the presentation of financial statements, and to find out and analyze BPKAD BPKAD financial statements on the application of cash flow statements with SAP No. 01 of 2010 concerning the presentation of financial statements and with SAP No. 03 of 2010 concerning the presentation of cash flow statements.The analytical tool used is a comparative analysis that compares the presentation of balance sheet and cash flow statements against SAP in 2010, and was tested using the J.Champion formula. The results of this study are the presentation of the 2017-2016 balance sheet in accordance with SAP No. 01 of 2010, and the presentation of cash flow statements for 2017-2016 in accordance with SAP No. 01 and SAP No. 03 of 2010.